Danmarks position i det internationale elitesportskapløb - post Beijing - Storm, Rasmus Klarskov (Forum for Idræt, 2009)
Artiklen vurderer på baggrund af med Team Danmarks resultatkontrakter med Kulturministeriet og Team Danmarks efterspørgsel efter flere penge til elitearbejdet, den danske position i den internationale elitesportskapløb og indetificerer de problemstillinger, som organiseringen af dansk eliteidræt står over for. The Danish Standings in the International Sporting Arms Race – Post Beijing The development within international elite sport has launched a global sporting arms race. As pointed out by international scholars, more and more countries develop medal capability investing ever more resources in the fight for international success. This international trend has affected the Danish context resulting in a growing political focus on international results. On the basis of the recent Danish rankings in the Olympic Games in China, the debate on Danish elite sport has intensified. Although the number of Danish medals reached the goal set for the games, the Danish elite sport organization, Team Denmark, subsequently demanded more capital for elite sport development claiming that without increased resources, Denmark will face decreasing results in the future. This article analyses the Danish position in the international sporting arms race together with identifying the challenges of Danish elite sport. Including identified factors of international sporting success, a brief performance analysis of the Danish model is carried out. Finally the appropriateness of increased funding for Team Denmark is discussed.